A Multi‐Granularity Density Peak Clustering Algorithm Based on Variational Mode Decomposition. Issue 4 (1st July 2021) - Ziwen, GU; Peng, LI; Xun, LANG; Yixuan, YU; Xin, SHEN; Min, CAO
Abstract : Density peak clustering (DPC) can identify cluster centers quickly, without any prior knowledge. It is supposed that the cluster centers have a high density and large distance. However, some real datasets have a hierarchical structure, which will result in local cluster centers having a high density but a smaller distance. DPC is a flat clustering algorithm that searches for cluster centers globally, without considering local differences. To address this issue, a Multi‐granularity DPC (MG‐DPC) algorithm based on Variational mode decomposition (VMD) is proposed. MG‐DPC can find global cluster centers in the coarse‐grained space, as well as local cluster centers in the fine‐grained space. In addition, the density is difficult to calculate when the dataset has a high dimension. Neighborhood preserving embedding (NPE) algorithm can maintain the neighborhood relationship between samples while reducing the dimensionality. Moreover, DPC requires human experience in selecting cluster centers. This paper proposes a method for automatically selecting cluster centers based on Chebyshev's inequality. MG‐DPC is implemented on the dataset of load‐data to realize load classification. The clustering performance is evaluated using five validity indices compared with four typical clustering methods. The experimental results demonstrate that MG‐DPC outperforms other comparison methods.